Measuring Agile Organization Implementation: A Case Study of Financial Education and Training Agency, Ministry of Finance - Effendi, Irwan Harisman; Ghazali, Achmad (Yayasan Riset dan Pengembangan Intelektual, 2026)
The concept of an agile organization has expanded beyond the private sector and is increasingly being adopted within the public sector, including government institutions. One such organization that has begun to implement this concept is the Financial Education and Training Agency (BPPK). As part of the Ministry of Finance of the Republic of Indonesia, BPPK is actively preparing for the comprehensive implementation of an agile organization framework. To assess the current state and readiness of BPPK in adopting this concept, an evaluation was conducted to examine the implementation of agile organization characteristics. This evaluation is based on the five core characteristics of an agile organization: strategy, structure, process, people, and technology. The findings of the evaluation suggest that BPPK has successfully integrated several key characteristics of an agile organization. Notably, the areas of structure and technology stand out, with BPPK designing and creating an open physical and virtual environment that empowers employees to perform their roles more effectively within a conducive setting. Furthermore, BPPK has developed state-of-the-art technology to support the execution of business processes, thereby enhancing work effectiveness and accountability. However, other agile organization characteristics, such as strategy, process, and people, still require further attention and focus from BPPK to fully implement this concept. These characteristics have been assessed as being below the average score for each component, indicating considerable room for improvement. Additionally, a change management strategy was mapped using the ADKAR model. This strategy focuses on five key areas: building awareness, fostering desire, providing knowledge, ensuring ability, and establishing reinforcement. It is anticipated that the successful application of this strategy will facilitate a smooth transition to an agile organization at BPPK and minimize employee resistance to the change process.